Aerothermodynamic Effects and Modeling of the Tangential Curvature of Guide Vanes in an Axial Turbine Stage. (23rd May 2017) - Shieh, Tzong-Hann
Abstract : By tangential curvature of the stacking line of the profiles guide vanes can be designed, which have on both ends an obtuse angle between suction side and sidewall. This configuration, according to literature, is capable of reducing secondary loss. This type of vanes develops considerable radial components of the blade force and effects a displacement of the meridional flow towards both sidewalls. In this paper we work with a finite-volume-code for computations of the three-dimensional Reynolds averaged Navier-Stokes equations for an axial turbine stage with radial and two types of tangentially curved guide vanes. With computational results, mathematical formulations are developed for a new flow model of deflection of such blades that are formally compatible with the assumption of a rotation-symmetrical flow and with the existing throughflow codes, in order to predict the deflection angle over the blade height for the tangential leaned and curved blades.